Addressing the (ELF)ant in the Room: The Views of Polish Teachers of English on English as a Lingua Franca - Paciorkowski, Tomasz (2022)
Students' and teachers’ attitudes towards English as a lingua franca (ELF) have been a fertile research area in recent years. Nevertheless, Polish in-service teachers' views have been neglected. The present study addresses this gap in research and examines the beliefs and attitudes held by a group of eighty Polish in-service teachers towards ELF. The participants completed a survey that consisted of quantitative and qualitative questions. The data were analysed using both statistical and thematic analysis. The results obtained in the study suggest that teachers' awareness and views on ELF are rather negative and distrustful. They mostly see ELF as a useful and necessary concept, yet continue recognising native pronunciation, grammar, and vocabulary models as their teaching goals. The data also suggest that a gap in teacher education programmes exists as the respondents either do not know or do not believe that Outer Circle Englishes are legitimate native varieties. Teachers also retain stereotypical views on Polish and native accents, perceiving the latter positively and the former negatively. This paper strongly suggests that teacher education programmes in Poland should ensure students and future teachers are aware of developments in the field of English Language Teaching.
Keywords: ELF; Polish; FL teachers; Poland; FL teachers’ attitudes; FL teachers’ beliefs